Reductive arene ortho-silanolization of aromatic esters with hydridosilyl acetals1. Issue 18 (4th March 2015) - Hua, Yuanda; Asgari, Parham; Dakarapu, Udaya Sree; Jeon, Junha
<x xml:space="preserve">Abstract</x> The design and application of a single-pot, reductive arene C–H bond silanolization of esters for synthesis of ortho-formyl arylsilanols.